2019
DOI: 10.3390/ma12030463
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Reaction Injection Pultrusion for Continuous Glass Fiber-Reinforced Polyamide-6 Composites

Abstract: In this paper, glass fiber-reinforced polyamide-6 (PA-6) composites with up to 70 wt% fiber contents were successfully manufactured using a pultrusion process, utilizing the anionic polymerization of caprolactam (a monomer of PA-6). A novel thermoplastic reaction injection pultrusion test line was developed with a specifically designed injection chamber to achieve complete impregnation of fiber bundles and high speed pultrusion. Process parameters like temperature of injection chamber, temperature of pultrusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…In addition to carbon fibers, there are many other types of fibers that can be used as reinforcement [ 6 , 7 , 8 , 9 ]. In this paper, we choose to employ PET (Polyethylene terephthalate) fiber-reinforced thermoplastic composites (PFRTPCs) due to their numerous advantages.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to carbon fibers, there are many other types of fibers that can be used as reinforcement [ 6 , 7 , 8 , 9 ]. In this paper, we choose to employ PET (Polyethylene terephthalate) fiber-reinforced thermoplastic composites (PFRTPCs) due to their numerous advantages.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been studied that only a specific proportion of activated monomer and catalyst guarantees a complete reaction with a low amount of residual monomer [24]. Hence, there is a great interest in studying applications of T-RTM in reaction injection molding, pultrusion and vacuum infusion due to the rapid PA6 and reinforced PA6 polymerization process resulting in molded parts with excellent mechanical properties [17,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, dissolution and regeneration of cellulose I were believed to lead to a transformation to cellulose II, which was reported to be a more stable form of cellulose due to the anti-parallel packing of the single cellulose chains in contrast to the parallel packing in cellulose I [22]. In past studies, it was also revealed that the cellulose I structure was able to be maintained in the case of wood powder regenerated from wood solution in the ionic liquid [9]. In this study, the unchanged crystalline structure of cellulose I was attributed to the dissolution of only minimal amounts of cellulose.…”
Section: Crystallinitymentioning
confidence: 99%
“…Especially for the field of using bio-based polymer as a matrix resin to manufacture composite materials, more and more researchers have begun to devote themselves to the research in this field, because of the high rate of depletion of petroleum resources, and growing global environmental and social concerns [5][6][7][8]. Wood is one of the most abundant renewable resources on the earth and it should be a long-term goal to develop wood-based biocomposites to replace the petroleum-based composite materials that are not recyclable at present [9,10].…”
Section: Introductionmentioning
confidence: 99%